PENGARUH PEMUPUKAN BIO URIN KELINCI DAN NPK PADA VARIABEL VEGETATIF TANAMAN SORGUM (Sorghum bicolor L.) - Yuri Pricilia, Atika; Dyah Utami, Christa; Syarief, Mochamad (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2024)
SRabbit urine can be used as organic liquid fertilizer for sorghum (Sorghum bicolor L.) because this plant require higher N nutrient than other nutrients. This study aims to obtain a combination of Rabbit Bio Urine (BUK) fertilizer concentration and NPK fertilizer dosage that can give the best results on the growth of sorghum plants (Sorghum bicolor L.). The research method used is a non-factorial Randomized Group Design (RAK) consisting of 6 levels, namely: P1 (BUK 0 ml/L + 100% NPK), P2 (BUK 41 ml/L + 80% NPK), P3 (BUK 27 ml/L + 80% NPK), P4 (BUK 18 ml/L + 80% NPK), P5 (BUK 9 ml/L + 80% NPK), and P6 (BUK 5 ml/L + 80% NPK). The application of rabbit bio urine fertilizer gives a real effect on the parameters of plant height and stem diameter at the age of 36 HST and 42 HST. In the parameter of the number of leaves, rabbit bio urine fertilizer and NPK gave no significant effect at all observation times. The P2 treatment (BUK 41 ml/L + NPK 80%) gave the highest results in the parameters of plant height at the age of 36 HST and 42 HST which amounted to 98,1 cm and 123,7 cm. In the parameter of stem diameter, the highest result was obtained by P1 (BUK 0 ml/L + NPK 100%) which amounted to 14,8 mm. . Keywords : N Nutrient, Rabbit Urine Bio Fertilizer, Sorghum